Tuberculin skin tests among medical students at risk for nosocomial transmission of Mycobacterium tuberculosis in Yazd, Iran - Behnaz, Fatemah; Mohammadzadeh, Mahmoud; Mohammadzade, Golnaz (International Journal of Infection Control, 2013)
Tuberculosis is an important public health issue throughout the world. Medical students as other health care workers are exposed to tuberculosis during their clinical rotations. The objective of this study was to evaluate latent tuberculosis infection in preclinical medical students and new infections during clinical rotations. A prospective cross sectional study was performed between 2008 and 2011 in Yazd by serial Tuberculin Skin Test in medical students. Medical students who have passed their 3.5 year preclinical stage were invited to participate in a 3-step PPD study before starting their clinical rotations .They were examined initially for BCG scar. In the first skin test, induration ≥10 mm was taken as positive. Students with initial negative test were retested 14 days later to identify boosting effect. Third test was done between 1to 3 years after the second step. Seventy medical students were invited to study, 54 participated in the study (77.1%). In the first test, 39.6% (95% CI 26-53.2%) had positive skin test≥10mm.In the second step 10 mm increase in induration was observed in one student without scar of BCG and 7 mm increase in induration was seen in another student. In the third step eight students 20.5% (95% CI, 7.83% to 33.17%) converted from negative to positive (TST≥10mm) during the period of study. Tuberculosis is an occupational infection among medical students. As a result, implementation of an effective tuberculosis infection control program is mandatory for prevention of tuberculosis among medical students.